Możliwość religii w obliczu współczesnego pluralizmu - Torzewski, Antoni (Humaniora. Czasopismo Internetowe, 2021)
Nowadays, very often in connection with postmodern philosophy, there appears a question of a normative call for pluralism. The argumentation made by postmodernists focuses mostly on the notions of violence and of metaphysics which, according to them, is a theoretical ground for violence. In the following paper we will try to present the possibile justification of this normative call, the reception of this call on Polish and international grounds, and also we will try to present how, in the face of this call, religion can function. To do this we will show concepts of religion; the first concept by Janusz Salamon (not connected to postmodernism) and the second by Gianni Vattimo (strictly postmodern).